Комплексний метод хірургічного лікування поширених гнійно-некротичних флегмон у хворих із цукровим діабетом - Кутовий, О. Б.; Косульников, С. О.; Карпенко, С. І.; Кравченко, К. В.; Тарнопольський, С. О.; Косульникова, Л. Ф. (Clinical Endocrinology and Endocrine Surgery, 2009)
The number of patients suffering from diabetes mellitus grows all the time. 5 to 10% of diabetes mellitus patients are being operated on each year in the surgical department with gastrointestinal disease while surgeons of purulent inflammatory departments operate 40% of such patients. 36 patients with extensive purulent necrotic phlegmons have been operated on with affected area from 40 to 1800 cm2. A complex method of surgical treatment of extensive purulent phlegmons is suggested where layered separation and turning the tissue away is used for mechanical sanation , treatment of the wounded area with napkins soaked with a composition of oxidants. After completing the sanation, the wound is covered with napkins soaked in the mixture of oxidants and is afterwards covered with a piece of skin that should be fixated it in the anatomical position. This method protects the wound from loosing plasma and lymph, preserves the skin and reduces lethality in three times. While carrying out systematic reconstructive operations on diabetes mellitus patients it is recommended not to take antibiotic prophylaxis but antibiotic therapy.